Introduction to East African Range Livestock Systems Study/Kenya - International Livestock Centre for Africa (International Livestock Centre for Africa, 1981)
Examines the interdisciplinary research being pursued by the ILCA East African Range Livestock Systems Study (EARLSS) team in Kenya, discussing the rationale for an interdisciplinary aproach to the study, factors which led to the concentration of the team's investigation on Maasai pastoralists, and background information on Kenya's Kajiado District & on the three group ranches where the study is focused. Describes the research design & methodology adopted by the EARLSS team, including the initial inventory survey, sampling procedures, dif. components of the study and types of analysis to be performed.